2006
DOI: 10.1101/gad.385706
|View full text |Cite
|
Sign up to set email alerts
|

A glycolytic enzyme, enolase, is recruited as a cofactor of tRNA targeting toward mitochondria in Saccharomyces cerevisiae

Abstract: In many organisms, mitochondria import nuclear DNA-encoded small RNAs. In yeast Saccharomyces cerevisiae, one out of two cytoplasmic isoacceptor tRNAs Lys is partially addressed into the organelle. Mitochondrial targeting of this tRNA was shown to depend on interaction with the precursor of mitochondrial lysyl-tRNA synthetase, preMsk1p. However, preMsk1p alone was unable to direct tRNA targeting, suggesting the existence of additional protein factor(s). Here, we identify the glycolytic enzyme, enolase, as such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 56 publications
3
134
0
2
Order By: Relevance
“…It also involved tRNA transport to the mitochondria in yeast (13). It remains to be determined whether this newly discovered function is related in any way to the heat-stability of enolase.…”
Section: Features Of Heat-stable Proteins In E Colimentioning
confidence: 99%
“…It also involved tRNA transport to the mitochondria in yeast (13). It remains to be determined whether this newly discovered function is related in any way to the heat-stability of enolase.…”
Section: Features Of Heat-stable Proteins In E Colimentioning
confidence: 99%
“…After the early observation of the presence of a cytoplasmic tRNA CUU Lys in Saccharomyces cerevisiae mitochondria (7), import of cytoplasmic tRNA CUG Gln was also demonstrated (8). Further studies showed that these tRNAs are imported by different mechanisms (8)(9)(10). The question of import into human mitochondria has never been addressed for its own sake.…”
mentioning
confidence: 99%
“…This strongly suggests that the MLR proteins are translated next to mitochondria, although the reason for this remains obscure. In some cases, this phenomenon may favor the formation of nucleo-proteocomplexes in the vicinity of mitochondria, as for Msk1, the mitochondrial lysyl-tRNA synthetase, which guides the import of tRNA Lys toward mitochondria (Entelis et al, 2006). To describe the MLR phenomenon in more detail, we developed two highly sensitive methods to: 1) quantify, in vitro, the amount of mitochondrial-associated mRNA and 2) to visualize, in situ, the localization of some mRNA species.…”
Section: Introductionmentioning
confidence: 99%